2015
DOI: 10.1007/s00018-015-1950-y
|View full text |Cite
|
Sign up to set email alerts
|

Splitting up the powerhouse: structural insights into the mechanism of mitochondrial fission

Abstract: Mitochondria are dynamic organelles whose shape is regulated by the opposing processes of fission and fusion, operating in conjunction with organelle distribution along the cytoskeleton. The importance of fission and fusion homeostasis has been highlighted by a number of disease states linked to mutations in proteins involved in regulating mitochondrial morphology, in addition to changes in mitochondrial dynamics in Alzheimer's, Huntington's and Parkinson's diseases. While a number of mitochondrial morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 143 publications
(222 reference statements)
0
39
0
Order By: Relevance
“…The process begins with the translocation of Drp1 from the cytosol to the outer mitochondrial membrane where it interacts with various proteins, including Mff and Fis1, prior to cleavage plane formation. 33 Surprisingly, the most significant change in expression in SH-N-Myc cells was a 2.5-fold increase in the DRP1 transcript (Figure 3b, left). The MFF and FIS1 transcripts were also increased, albeit by >50% and did not rise to the level of significance.…”
Section: Resultsmentioning
confidence: 92%
“…The process begins with the translocation of Drp1 from the cytosol to the outer mitochondrial membrane where it interacts with various proteins, including Mff and Fis1, prior to cleavage plane formation. 33 Surprisingly, the most significant change in expression in SH-N-Myc cells was a 2.5-fold increase in the DRP1 transcript (Figure 3b, left). The MFF and FIS1 transcripts were also increased, albeit by >50% and did not rise to the level of significance.…”
Section: Resultsmentioning
confidence: 92%
“…Biochemical and structural studies indicated that the mechanisms of DLP1‐induced mitochondrial fission were similar to those by other members of the dynamin‐superfamily (Richter et al ., 2015). DLP1 recruited to the outer membrane of mitochondria assembles into a ring structure, which induces the scission of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…At the mitochondria, Drp1 oligomerizes into higher-order spirals, which triggers GTP hydrolysis and subsequent constriction of the mitochondria [4,37]. Drp1-driven constriction is sufficient to narrow the mitochondrial diameter but insufficient to promote its complete severing [37,38]. Recently, Lee et al demonstrated that dynamin-2 is recruited to sites of Drp1-mediated constriction and severs the mitochondria to complete mitochondrial fission [39].…”
Section: Mitochondrial Dynamics Machinerymentioning
confidence: 99%